Hubungan Mutu Pelayanan Dengan Loyalitas Pelanggan Jasa Pengiriman Paket Pada Kantor Pos Kota Depok - Rahmawati, Emma; Hubeis, Musa (IPB University, 2011)
fice were (1) To identify the relationship between service quality and customer loyalty; (2) To analyze the relationship strength between service quality and customer loyalty; (3) Assessing the service quality level by Depok City Post Office. The data collecting were primary and secondary data. Convenience sampling was chosen as sampling technique. The research analyze by descriptive analysis, Importance Performance Analysis (IPA), Range and Rank Spearman correlation test, and processed by Microsoft Excel 2007 and Software SPSS 17.0 version for Windows. The study by IPA showed the attribute spread out around all quadrant with the majority attributes placed on quadrant III, however the study will be focused on attributes placed Quadrant I: completly of information media, quick service and complaint service, which are the main important factors to improve. The research finding was proven the customer is categorize as loyal customer. The analysis of work attributes level showed reliability has no relation with loyality. The Relationship between Good Quality of Customer Service and Customer Packaging Delivery Service Loyalty in Depok City Post Office is strong showed by r = 0,277.